EXPERIENCE OF LONG-TERM TERIPARATIDE USE FOR THE TREATMENT OF POSTOPERATIVE HYPOPARATHYROIDISM ASSOCIATED WITH OSTEOPOROSIS IN ELDERLY PATIENT - G. A. Batrak; A. N. Brodovskaya; S. E. Myasoedova (Klinicist)
The aim of study is to reflect the possibilities and effectiveness of teriparatide for the treatment of postoperative hypoparathyroidism associated with severe systemic osteoporosis, based on the data of the clinical case.Materials and methods. Patient N., aged 69, having a history of resection of 2/3 of the stomach according by Bilrot-2, urolithiasis, hypertension; since 2011 has been repeatedly hospitalized in National Medical Research Centre of Endocrinology, Ministry of Health of Russia, for secondary hyperparathyroidism and severe systemic osteoporosis. In 2016 thyroidectomy was performed in connection with papillary thyroid cancer and removal of left parathyroid gland adenoma, after which the patient developed postoperative hypoparathyroidism with severe uncontrolled hypocalcemia. As a replacement therapy, a synthetic analogue of parathyroid hormone, teriparatide, was used. For this work we used epicrisis of 2011–2016, as well as the results of the patient’s examination performed during the inpatient treatment in the Endocrinology Department of City Clinical Hospital № 4 (Ivanovo) from 2016 to 2018.Results. As a result of treatment with teriparatide in this patient, according to the results of a three-year follow-up, there is a positive clinical effect in the form of absence of convulsive syndrome, normalization of total and ionized calcium levels, absence of new compression fractures of vertebral bodies. Since the recovery of parathyroid gland function after surgery has not occurred, the use of this drug to the patient is recommended for the life term.Conclusion. The study describes a clinical case involving teriparatide as a therapy for postoperative hypoparathyroidism in combination with severe systemic osteoporosis and impaired calcium absorption in an elderly patient. The clinical effect of this type of treatment over a period of 3 years was proved in the form of normalization of phosphorus-calcium metabolism and the processes of bone remodeling in the absence of any side effects.